COVID-19 Vaccination Attitudes With Neuromyelitis Optica Spectrum Disorders: Vaccine Hesitancy and Coping Style - Xu, Yafang; Cao, Yanpei; Ma, Yue; Zhao, Yan; Jiang, Hong; Lu, Jiahong; Zhao, Chongbo; Quan, Chao (Frontiers in Neurology, 2021)
Background: Vaccination is an important method by which to stop the spread of coronavirus disease 2019 (COVID-19) in a population. Patients with neuromyelitis optica spectrum disorders (NMOSD) have an unstable immune function and receive immunosuppressive therapy frequently, so they are hard to decide to receive the vaccination. Our study investigated the vaccine hesitancy and coping styles in patients with NMOSD to analyze the relationship between vaccine hesitancy and coping styles, and elucidate the factors influencing vaccine hesitancy. Methods: A convenient sampling method was used to recruit participants. The Adult Vaccine Hesitancy Scale and Medical Coping Modes Questionnaire were used to measure the vaccine hesitancy and coping style of the participants. Pearson correlation, multiple stepwise, linear regression, and one-way analysis of variance were used to analyze the data. Results: A total of 262 NMOSD patients were investigated. The score of vaccine hesitancy in NMOSD patients is lower (21.13 ± 4.355) than 25 points which indicated the patient is not considered to have vaccine hesitancy. The score for vaccine hesitancy was negatively correlated with the confrontation and avoidance coping styles (r= −0.481and r=0.423). That adoption of the coping styles of confrontation and avoidance as well as the residence of the patient were predictors of vaccine hesitation in NMOSD patients (R2(adj)=0.29, P<0.001). In addition, the vaccine hesitancy scores of NMOSD patients residing in rural areas were significantly higher than those of patients living in urban areas (P < 0.01). Comparing with each level of education, the scores were not statistically significant in vaccine hesitancy and coping styles (P>0.05). Conclusions: This study reveals that the NMOSD patients are not considered to have vaccine hesitancy, Patients who tend to adopt confrontation and avoidance coping styles have less vaccine hesitancy. Health authorities and medical specialist teams should strengthen effective vaccination information for patients with NMOSD, such as expert consensus or guidelines through various media to help them with decision-making. The significance of vaccination, the safety and side effects of COVID-19 vaccination, and predicting epidemiological trends of COVID-19 should be emphasized. More attention should be paid to NMOSD patients who live in rural areas.